SUSTAINABLE SHRIMP (LITOPENAEUS VANNAMEI) FARMING THROUGH EFFICACIOUS BIOFLOC MANAGEMENT ENHANCES WATER QUALITY, GROWTH, AND SURVIVAL RATES. - Vivekananda Babu11, Ayyaru Gopalakrishnan*, (Chelonian Research Foundation, 2023)
Profitability in aquaculture is directly proportional to the quantum of biomass produced per harvest. With the utilization of scientifically improvised methods like biofloc management there is high probability to grow more biomass from limited space and attain better financial success in eco-friendly methods. Moreover, because of the great protein value of shrimps, huge economic potential, vulnerability to disease and changes in weather, adoption of biofloc technology has become popular. Current studies focus on biofloc innovations to address challenges of poor survival, growth, and water quality management in Litopenaeus vannamei culture which are necessary to minimise disease prevalence and loss in shrimp farming. Keywords: Litopenaeus vannamei, Biofloc innovation, Survival, Water quality management